Meaning and the Post-Parental Couple - Lantz, James E. (Journal of religion and health, 1999)
An existential approach to the treatment of post-parental couples is presented along with seven brief case illustrations of the described treatment approach. A descriptive clinical study that reviews changes made by twenty-three post-parental couples in existential treatment between 1990 and 1995 is also provided to document the usefulness of an existential treatment approach with post-parental couples.